MARINE SEDIMENT CHARACTERISTICS AT KARIMUN JAVA SEA BASED ON STRATIGRAPHIC PROFILE ANALYSIS, TOTAL SUSPENDED SOLID (TSS) AND GRAIN-SIZE ANALYSIS (GRANULOMETRY) - Suryantini Suryantini; Aris Ismanto; Indarta Kuncoro Aji; Dwi Fajar Saputri; Helfinalis Helfinalis (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2011)
A sedimentology survey was conducted during “Pelayaran Kebangsaan” research activities with a marine vessel of